Thyroid profile in type 2 diabetes mellitus - Dave, Mahesh; Saini, Hazari Lal; Gupta, Ankit; Choudhary, Jitendra Singh; Burli, Aniruddha (International Journal of Advances in Medicine, 2019)
Background: Diabetes mellitus is an endocrine disorder which involves multiple organ systems and leads to significant morbidity and mortality. Diabetes mellitus has been defined as “A metabolic syndrome characterized by chronic hyperglycemia and disturbance of carbohydrate, fat and protein metabolism associated with absolute or relative deficiency in insulin secretion and or insulin action”. Thyroid diseases are also a common endocrinopathy seen in the adult population. Thyroid hormones are intimately involved in cellular metabolism. The present work is a modest attempt to study the prevalence of thyroid disorders in patients with type 2 diabetes mellitus. Methods: The study was carried out in total 108 diabetic patients without known thyroid disorder admitted in various Medical wards of R.N.T. Medical college and attached group of hospitals, Udaipur. It was a cross Sectional study done over a period of 10 months. Results: In the present study, 13% of patients with type 2 diabetes mellitus had abnormal thyroid profile. Out of which the most common presentation was sub clinical hypothyroidism found in 9.25% followed by1.9% had overt hypothyroidism and 1.9% had sub clinical hyperthyroidism. In persons with abnormal thyroid profile 85.7% were females and 14.3% were males which was statistically significant. Conclusions: Prevalence of thyroid dysfunction is common among T2DM patients and is higher in females than in males. There is no significant correlation between thyroid dysfunction and age, diabetes control, family history, type of treatment and HbA1c level in diabetic patients.